Effect of Non genetic Factors on Weight Traits of Local Tarai Goats under Farmers’ Managed Condition - Bhattarai, Nirajan; Sapkota, Saroj (Nepal Journal of Science and Technology, 2012)
A field study was carried out to characterize, evaluate and estimate the effect of non-genetic factors on the productive and reproductive performance of local Terai goats during March 2006 to February 2007 in Siraha, district. Altogether 206 dams and 318 kids of different age groups were identified for this study and data on productive performance was collected based on periodic field monitoring. The mean body weight of kids at birth, pre-weaning, weaning, and post weaning at 6 and at 8 months were was 2.23±0.04, 5.75±0.16, 10.18±0.23, 13.67±0.28, and 19.31±0.44 kg, respectively. Among the non-genetic factors, parity significantly (p<0.05) influenced but only to post-weaning weight of kids at 8 months. Post weaning weight of kids at 6 and 8 months significantly differed (p<0.05) with respect to sex, and birth type significantly differed to the body weight at birth (p<0.001), pre-weaning (p<0.01), weaning and at 6 months post-weaning (p<0.05) age. Thus, the results of this study suggested that the overall productivity of local Terai goat breed could be improved through selective breeding practices, especially by considering the non genetic factors such as, birth type and sex of kids. DOI: http://dx.doi.org/10.3126/njst.v12i0.6479 Nepal Journal of Science and Technology 12 (2011) 51-54